Forty years of doing second language testing, curriculum, and research: So what?. (14th March 2017) - Brown, James Dean
Abstract : I started out as a budding English as a second language (ESL) teacher in 1976 at UCLA where I went through the M.A. TESL (Teaching English as a Second Language) and Applied Linguistics Ph.D. programs. Sadly, those two programs were 'disestablished' in 2014, which provides a stark lesson to any departments that think they are hot stuff thatnothing lasts forever . Nonetheless, my training in those programs provided me with an excellent start down three professional paths: second language testing, curriculum development, and research methods.